Bismuthene for highly efficient carbon dioxide electroreduction reaction - Yang, Fa; Elnabawy, Ahmed O.; Schimmenti, Roberto; Song, Ping; Wang, Jiawei; Peng, Zhangquan; Yao, Shuang; Deng, Ruiping; Song, Shuyan; Lin, Yue; Mavrikakis, Manos; Xu, Weilin (Nature communications, 2020)
Bismuth (Bi) has been known as a highly efficient electrocatalyst for CO 2 reduction reaction. Stable free-standing two-dimensional Bi monolayer (Bismuthene) structures have been predicted theoretically, but never realized experimentally. Here, we show the first simple large-scale synthesis of free-standing Bismuthene, to our knowledge, and demonstrate its high electrocatalytic efficiency for formate (HCOO − ) formation from CO 2 reduction reaction. The catalytic performance is evident by the high Faradaic efficiency (99% at −580 mV vs. Reversible Hydrogen Electrode (RHE)), small onset overpotential (<90 mV) and high durability (no performance decay after 75 h and annealing at 400 °C). Density functional theory calculations show the structure-sensitivity of the CO 2 reduction reaction over Bismuthene and thicker nanosheets, suggesting that selective formation of HCOO − indeed can proceed easily on Bismuthene (111) facet due to the unique compressive strain. This work paves the way for the extensive experimental investigation of Bismuthene in many different fields. Stable free-standing two-dimensional Bi monolayer (Bismuthene) structures have been predicted theoretically, but never realized experimentally. Here, the authors show a large-scale synthesis of free-standing Bismuthene and its electrocatalytic activity for CO 2 reduction to formate.